# 2x(x-3)=8

## Simple and best practice solution for 2x(x-3)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2x(x-3)=8 equation:

Simplifying
2x(x + -3) = 8
Reorder the terms:
2x(-3 + x) = 8
(-3 * 2x + x * 2x) = 8
(-6x + 2x2) = 8
Solving
-6x + 2x2 = 8
Solving for variable 'x'.
Reorder the terms:
-8 + -6x + 2x2 = 8 + -8
Combine like terms: 8 + -8 = 0
-8 + -6x + 2x2 = 0
Factor out the Greatest Common Factor (GCF), '2'.
2(-4 + -3x + x2) = 0
Factor a trinomial.
2((-1 + -1x)(4 + -1x)) = 0
Ignore the factor 2.
Subproblem 1Set the factor '(-1 + -1x)' equal to zero and attempt to solve:
Simplifying
-1 + -1x = 0
Solving
-1 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + -1x = 0 + 1
Combine like terms: -1 + 1 = 0
0 + -1x = 0 + 1
-1x = 0 + 1
Combine like terms: 0 + 1 = 1
-1x = 1
Divide each side by '-1'.
x = -1
Simplifying
x = -1
Subproblem 2Set the factor '(4 + -1x)' equal to zero and attempt to solve:
Simplifying
4 + -1x = 0
Solving
4 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + -1x = 0 + -4
Combine like terms: 4 + -4 = 0
0 + -1x = 0 + -4
-1x = 0 + -4
Combine like terms: 0 + -4 = -4
-1x = -4
Divide each side by '-1'.
x = 4
Simplifying
x = 4Solutionx = {-1, 4}`

## Related pages

square roots of 196roman numerals 19811.0625 as a fractionderivative of e 9xgraph of 5xgraph of y sinx310-40factorization of 12017x44x2 4x 1graph the equation y 2x 3800-256find the prime factorization of 427222-19y225-144graph x 4y 8greatest prime factor of 6870-68common multiples of 9solve sin x sinx 1 0derive ln 2xhow to graph x 3y0.6875 as a fractionderive ln x 277 in roman numeralsgraph x 2y 10roman numerals for 19692x 4y 8greatest common factor of 48 and 64prime factorization of 24377 in roman numeralsbsquared2x 2 5x 2 factorsolving binomial equations calculator2x 2y 5z 2x y 3zx 2 12x 4 0ln x 1 derivative86x or 64x9x 2 4y 2 362000-7508.1.3solve y 5xq qwertyuiopasdfghjklzxcvbnmsolving two step equations calculatorsquare root of 9216simplify quadratic equations calculatordifferentiation of sin 2xintegral exp xsqrt 192cos 2x sin x6yisolve y 3x 1cos 4xx2y xy2what is 12x5sinh 2x cosh 2xprime factorization 156simplify 2x 2-5x-3equations with fractions calculator180-152sin 2pix 2 cubedgraph x 7yfraction from least to greatest calculatorfourth derivative calculatory42percents to fraction calculator4x 5y 201944 in roman numeralssolve equations calculator with fractionscos30least to greatest fractions calculator8x squaredhow to graph y 3x500-171cox and cosv2 u2 2asfind the prime factorization of 8